2019
DOI: 10.1002/jcu.22721
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound‐guided needle biopsy of large thyroid nodules: Core needle biopsy yields more reliable results than fine needle aspiration

Abstract: Purpose The objective of this study was to compare the false negative rate, sensitivity and false positive rate of ultrasound (US)‐guided fine needle aspiration (FNA) with those of US‐guided core needle biopsy (CNB) for large thyroid nodules ≥2.0 cm, which reportedly have an increased risk of thyroid malignancy. Methods We retrospectively studied surgically confirmed thyroid nodules that had preoperative US‐guided FNA or CNB between March 2005 and December 2013. We reviewed nodule size, sonographic features, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 35 publications
(120 reference statements)
0
10
0
Order By: Relevance
“…But in nodules larger than 40 mm, a significantly higher inconclusive rate was seen in malignant nodules with FNA while no significant differences were seen between malignant and benign nodules with CNB. High false-negative rates have been reported for FNA in large thyroid nodules ( 23 24 25 26 27 ), leading to more surgeries for diagnostic purposes. Based on our findings, CNB shows potential as a tool that allows clinicians to make more conclusive preoperative diagnoses of large thyroid nodules that can guide clinicians when they are deciding on how to approach patient management.…”
Section: Discussionmentioning
confidence: 99%
“…But in nodules larger than 40 mm, a significantly higher inconclusive rate was seen in malignant nodules with FNA while no significant differences were seen between malignant and benign nodules with CNB. High false-negative rates have been reported for FNA in large thyroid nodules ( 23 24 25 26 27 ), leading to more surgeries for diagnostic purposes. Based on our findings, CNB shows potential as a tool that allows clinicians to make more conclusive preoperative diagnoses of large thyroid nodules that can guide clinicians when they are deciding on how to approach patient management.…”
Section: Discussionmentioning
confidence: 99%
“…There is something of a debate surrounding the topic of whether size has any relevance to diagnostic accuracy. A number of studies suggest that larger nodules with benign cytology nevertheless harbour a greater risk for malignancy and a higher rate of false‐negative cytology results 21‐24 . Some authors argue that larger size (≥30 mm) may influence clinical decision making because FNA has decreased reliability in such nodules.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study suggested the superiority of US-guided core needle biopsy over US-guided FNA with lesser false negativity and better sensitivity for large thyroid nodules (≥2.0 cm) to diagnosis thyroid malignancy [25]. An earlier study assessed Figure 2.…”
Section: Discussionmentioning
confidence: 99%